2019
DOI: 10.3390/met9080845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auto-Tuning on Serrated Flow Behavior

Abstract: The mechanical response of a servo-hydraulic testing system is affected by the stiffness of test specimens. An adaptive controller helps in auto-tuning the system by setting the optimal proportional-integral-derivative values for the subsequent test as the stiffness changes. This paper presents the effect of auto-tuning of various channels on the flow response of several commercial Al and Mg alloys and a mild steel. Strain-controlled monotonic tensile tests were performed at a given strain rate of 1 × 10−4 s−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…A similar serrated flow phenomenon present in the hysteresis loops was also reported during strain-controlled LCF of Al-Zn-Mg alloy in a natural aging condition [39] and in other materials, e.g., annealed Zircaloy-2 [46], forged alloy 617M in the solution annealed condition [47], Inconel 718 superalloy [48], duplex Ti-6Al-4V and SP700 titanium alloys [49], and extruded AM50 magnesium alloy [50]. It should be noted that the serrated flow behavior is dependent on the strain rate and temperature [51][52][53]. Recently, Mohammed and Chen [52] observed that the serrations during uniaxial tensile testing disappeared after all the three (displacement, load, and strain) channels in the servo-hydraulic fatigue machine were auto-tuned due to the shielding effect for control stability.…”
Section: Tensile Propertiesmentioning
confidence: 55%
See 1 more Smart Citation
“…A similar serrated flow phenomenon present in the hysteresis loops was also reported during strain-controlled LCF of Al-Zn-Mg alloy in a natural aging condition [39] and in other materials, e.g., annealed Zircaloy-2 [46], forged alloy 617M in the solution annealed condition [47], Inconel 718 superalloy [48], duplex Ti-6Al-4V and SP700 titanium alloys [49], and extruded AM50 magnesium alloy [50]. It should be noted that the serrated flow behavior is dependent on the strain rate and temperature [51][52][53]. Recently, Mohammed and Chen [52] observed that the serrations during uniaxial tensile testing disappeared after all the three (displacement, load, and strain) channels in the servo-hydraulic fatigue machine were auto-tuned due to the shielding effect for control stability.…”
Section: Tensile Propertiesmentioning
confidence: 55%
“…It should be noted that the serrated flow behavior is dependent on the strain rate and temperature [51][52][53]. Recently, Mohammed and Chen [52] observed that the serrations during uniaxial tensile testing disappeared after all the three (displacement, load, and strain) channels in the servo-hydraulic fatigue machine were auto-tuned due to the shielding effect for control stability. However, in the present study the serrations are still observed even after auto-tuning of the strain channel.…”
Section: Tensile Propertiesmentioning
confidence: 99%